Protocol for evaluating physiological and psychological acclimatization mechanisms in Tibetan plateau environment: a clinical study of doctors from Peking Union Medical College Hospital - Xu, Hemiao; Yang, Daiyu; Li, Shuai; He, Kun; Bian, Macuo; Liu, Zhijuan; Xu, Chengli; Wu, Dong (Frontiers in Public Health, 2024)
IntroductionThe transition from low to high altitude environments is associated with a multifaceted series of physiological and psychological alterations that manifest over time. These changes are intricately intertwined, with physiological acclimatization primarily mediated through the regulation of hypoxia-inducible factor (HIF), which orchestrates the expression of critical molecules and hormones. This process extends to encompass the epigenome, metabolism, and other regulatory mechanisms. In the realm of psychological acclimatization, chronic hypoxia and changes in atmospheric pressure at high altitudes may contribute to decreased levels of neurotransmitters, with potential implications for mental health, particularly in relation to sleep quality. Despite significant advancements in our understanding of plateau acclimatization mechanisms in recent years, there remain many uncertain factors that necessitate further research.MethodsThis study is a single-center prospective observational study. It aims to utilize a series of physiological and medical instruments in conjunction with internationally recognized physiological and psychological questionnaires to monitor the dynamic shifts in the acclimatization ability of doctors from Peking Union Medical College Hospital. The monitoring will occur at seven distinct time points: pre-departure from Beijing, 1–7 days post-arrival at the Tibetan plateau during the acute phase of plateau hypoxic stress, and during the chronic phase of plateau hypoxic stress at 2 weeks, 3 months, 6 months, 12 months of residency in Tibet, and post-return to Beijing. Concurrently, a spectrum of omics analyses will be conducted, including comprehensive genomic, proteomic, and metabolomic assessments of blood leukocytes, fecal, and oral samples.